Quality Evaluation of Al-Rasheed Ready Concrete Mixture Plant By Using Six Sigma Approach (Journal of Engineering, 2012)
The objective of this research work is to evaluate the quality of central concrete plant of Al-Rasheed Company by using Six Sigma approach which is a measure of quality that strives for near elimination of defects using the statistical methods to improve outputs that are critical to customers. The fundamental objective of Six Sigma methodology is the implementation of a measurement-based strategy that focuses on process improvement and variation reduction to reach delighting customers, and then suggesting an improvement system to improve the production of concrete in Al-Rasheed State Contracting Construction Company. A field survey includes two parts (open and close questionnaire) that aimed to get the data and information required for achieving the research where the answers of questionnaire sample have led, during the application of DMAIC improvement cycle, to identifying the potential possible reasons that caused quality deviations in concrete works. Two programs have been used: First, ‘Sigma Level Calculator’ which is formulated by the researcher to measure the components of the processes performance. Second, ‘QI Macros Lean Six Sigma SPC Software 2011’ which uses the statistical tools of Six Sigma DMAIC methodology for: identifying the root causes of defects, analyzing the data, determining capability and stability of process. It is concluded that the processes sigma level for the concrete works quality is 2.41 σ and 181,070 DPMO which is considered too bad as compared with the current global competitio